Violation of the Kluberg-Stern-Zuber theorem in SCET - Martin Beneke; Mathias Garny; Robert Szafron; Jian Wang (Journal of High Energy Physics, 2019)
Abstract A classic result, originally due to Kluberg-Stern and Zuber, states that operators that vanish by the classical equation of motion (eom) do not mix into “physical” operators. Here we show that and explain why this result does not hold in soft-collinear effective theory (SCET) for the renormalization of power-suppressed operators. We calculate the non-vanishing mixing of eom operators for the simplest case of N -jet operators with a single collinear field in every direction. The result implies that — for the computation of the anomalous dimension but not for on-shell matrix elements — there exists a preferred set of fields that must be used to reproduce the infrared singularities of QCD scattering amplitudes. We identify these fields and explain their relation to the gauge-invariant SCET Lagrangian. Further checks reveal another generic property of SCET beyond leading power, which will be relevant to resummation at the next-to-leading logarithmic level, the divergence of convolution integrals with the hard matching coefficients. We propose an operator solution that allows to consistently renormalize such divergences.